2013
DOI: 10.1177/1866802x1300500105
|View full text |Cite
|
Sign up to set email alerts
|

Does Women's Presence Change Legislative Behavior? Evidence from Argentina, 1983–2007

Abstract: In scores of countries, the adoption of gender quotas has boosted the numbers of women elected to national legislatures. How does the growing presence of women affect legislative behavior regarding women's rights? Using an original dataset of all the bills submitted to the Argentine Congress between 1983 and 2007, we analyze the relationship between women's presence in Congress and the introduction and approval of bills related to women's rights. Our dataset allows us to compare three periods with varying leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 52 publications
1
49
1
3
Order By: Relevance
“…Moreover, scholars already know a great deal about legislative politics in Latin America (e.g., Morgenstern ; Morgenstern and Nacif ), and about the effects of Latin American legislators’ gender, ethnic, and political backgrounds (e.g., Htun, Lacalle, and Micozzi ; Jones ; Jones et al ; Saint‐Germain and Chavez Metoyer ; Schwindt‐Bayer ). Studying the classes Latin American legislatures come from is not a journey into the wilderness.…”
Section: Evidence From Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, scholars already know a great deal about legislative politics in Latin America (e.g., Morgenstern ; Morgenstern and Nacif ), and about the effects of Latin American legislators’ gender, ethnic, and political backgrounds (e.g., Htun, Lacalle, and Micozzi ; Jones ; Jones et al ; Saint‐Germain and Chavez Metoyer ; Schwindt‐Bayer ). Studying the classes Latin American legislatures come from is not a journey into the wilderness.…”
Section: Evidence From Latin Americamentioning
confidence: 99%
“…Scholars studying how gender and ethnicity affect legislator behavior in Latin America similarly emphasize the crucial agenda‐setting stage (Franceschet and Piscopo ; Htun, Lacalle, and Micozzi ; Schwindt‐Bayer ).…”
mentioning
confidence: 99%
“…In Latin America, women have increased their participation in national parliaments as a result of legislative quotas, but research is not conclusive when assessing their impact on gender equality policies. There is some agreement that the growing number of women in legislatures in Latin America increases attention on women's concerns, but women are more likely to affect the legislative process during agenda setting and bills initiation (Schwindt‐Bayer, ; Franceschet and Piscopo, ; Franceschet et al, ; Htun et al, ). In addition, despite a long legacy of maternalism and weak feminism in Latin America, women's presence in congress has expanded debate regarding gender equality policies such as contraception, gender‐based violence and family laws (Schwindt‐Bayer, ).…”
Section: Explaining Legislative Outcomes: An Institutional Frameworkmentioning
confidence: 99%
“…Examining data on bill initiation from the Honduras Congress from the 1990 to 1997, Taylor-Robinson and Health (2003) also find that female legislators dedicate a higher priority to women's rights issues. Similarly, Htun, Lacalle and Micozzi (2013) reinforce that congresswomen advocate more women's rights issues than their male colleagues. Using data on bills initiation from Argentine Congress from 1983 to 2007, the authors show that while the results confirm that women introduced more bills related to women's rights, on the other hand, the approval rates of these bills actually decline over time as female participation in Congress has increased.…”
Section: IImentioning
confidence: 85%
“…A key question that has emerged in the literature is about the relation between greater female representation and greater advocacy of female voter priorities. On the one hand, the literature has shown that female politicians have different political preferences and priorities than their male colleagues (Schwindt-Bayer 2006;Swers 2002;Taylor-Robinson and Health 2003;Htun, Lacalle and Micozzi 2013). On the other hand, few studies have investigated whether there is a straightforward relationship between female politicians and their advocacy of female voters' interests (Chattopadhyay and Duflo 2004;Clots-Figueras 2012;Svaleryd 2009).…”
Section: Introductionmentioning
confidence: 99%